A general solution for the removal of polydisperse aerosol particles and application to pool scrubbing. (4th July 2018) - Park, Sung Hoon; Park, Changhwan; Lee, JinYong; Lee, Byungchul
ABSTRACT: Pool scrubbing occurring in the containment of a nuclear reactor is an important mechanism for radioactive particle removal. In this article, an approximate analytical solution to the equation of particle removal with any possible combination of removal processes is suggested. Assuming that the particle size distribution can be approximated by a log-normal function, the reduction of total particle number and mass, and the changes in average particle size and polydispersity are expressed as explicit functions of their initial values, time, and the removal mechanism parameters. The solution is then applied to a pool scrubbing problem as an application example. The approximate solution derived in this study shows good agreement with the exact solution. The error, caused by an approximation for the slip correction factor, is potentially large only for the intermediate-size particles. However, the absolute error still remains small because the particle removal rate is minimum in that size range. The methodology adopted and the solution derived in this paper will be useful when only particle size distribution parameters are available without full information of whole size distribution.